Postoperative agitation syndrome in young children with perinatal damage to the central nervous system - V.I. Snisar; O.S. Pavlysh (Zaslavsky O.Yu., 2021)
One of the complications of the postoperative period in children is postanesthetic agitation, a significant emotional and uncontrollable worry, clouding of consciousness, feeling of anxiety and fear, inappropriate behavior, irritability, inconsolable crying, aggressive and negative attitude towards parents and medical staff. Postoperative agitation is very important for clinicians and hospitals, it has a risk of harming a patient, staying longer in the ward after anesthesia, and increasing the period of postoperative recovery. The frequency of postoperative agitation depends on age group. Most often agitation occurs in young children. There is evidence that agitation can also be due to the immature nervous system and a consequence of pathological conditions of the central nervous system (asthenoneurotic syndrome, encephalopathy, hyperactivity syndrome, perinatal posthypoxic and organic brain lesions, history of prematurity, epilepsy, psychophysical and speech delay, etc.). That is why the goal of our research was to study the patterns of clinical manifestations of postoperative agitation syndrome in children with prenatal damage to the central nervous system. The work was performed based on the analysis of the postoperative period in 109 young children: 59 patients with acquired hydrocephalus, who underwent ventriculoperitoneal shunting, and 50 children without neurological disorders in whom reconstructive surgeries were carried out. Depending on the type anesthetic management, each group was divided into two subgroups: children, who received inhalation anesthesia with sevoflurane, and those, who received total intravenous anesthesia using propofol. In the postoperative period, the behavior of children was assessed on a Pediatric Anesthesia Emergence Delirium scale 30 minutes after anesthesia was completed. Criterion for the development of agitation was the presence of excitement in a child with a score of ≥ 10 points. Study showed that young children with perinatal damage to the central nervous system and children whose anesthetic provision is carried out using sevoflurane are the most vulnerable to the development of agitation syndrome. Agitation in such children is more pronounced and longer. These cases require prediction, detection and active surveillance.